"Meds-in-Hand" Intervention to Reduce Critical Process Delays in Pediatric Human Immunodeficiency Virus Post-Exposure Prophylaxis. (29th April 2020) - Epstein, Rachel L; Penwill, Nicole; Clarke, Diana F; Hamilton, Sebastian; Horbowicz, Kevin; Dorfman, David; Moses, James M; Cooper, Ellen R
Abstract: Pediatric human immunodeficiency virus post-exposure prophylaxis is frequently indicated, but delays in medication receipt are common. Using plan-do-study-act cycles, we developed a multidisciplinary collaboration to reduce critical process delays in our pediatric emergency department. Interruptions decreased from a median 1 per month pre-intervention to zero per month during the intervention.